Chemical control of adult sourgrass in coffee crops, through various associations - Coelho, Vitor; Belutti Voltolini, Giovani; Rabelo Botrel Miranda, Gustavo; Mauro Costa Monteiro, José; de Oliveira Alecrim, Ademilson (Scientia Agraria Paranaensis, 2021)
Weed management in coffee plants is carried out largely through the adoption of chemical control, with the use of herbicides. In this context, one of the species that most affects the development of coffee plants, and due to its difficulty in control, is sourgrass. Above all, most sourgrass biotypes are not efficiently controlled with the herbicide glyphosate, which is the most used in coffee growing. Thus, the search for strategies that can minimize the damage caused by this weed, appears with increasing demand, due to the great damage to coffee plants. Therefore, the objective of this study was to evaluate the chemical control of adult sourgrass in coffee plants, through several associations. Treatment control efficiency was visually evaluated, where a scale ranging from 0 to 100 was used, with 0 corresponding to the absence of symptoms and 100 corresponding to the total control of weed plants by the action of herbicides, respectively. This evaluation method was used at 7, 14, 21, 28, 35 and 42 days after application. The mixture of the herbicides Fluazifop-p-butyl and Clethodim is more efficient in controlling sourgrass over time. The association of the herbicide ammonium glufosinate with systemic herbicides implies a reduction in the control capacity of sourgrass plants over time.